Molecular Assembly and Biosynthesis of Acetylcholinesterase in Brain and Muscle: the Roles of t-peptide, FHB Domain, and N-linked Glycosylation - Chen, Vicky P.; Luk, Wilson K.; Chan, Wallace K.; Leung, K. Wing; Guo, Ava J.; Chan, Gallant K.; Xu, Sherry L.; Choi, Roy C.; Tsim, Karl W. (Frontiers in Molecular Neuroscience, 2011)
Acetylcholinesterase (AChE) is responsible for the hydrolysis of the neurotransmitter, acetylcholine, in the nervous system. The functional localization and oligomerization of AChE T variant are depending primarily on the association of their anchoring partners, either collagen tail (ColQ) or proline rich membrane anchor (PRiMA). Complexes with ColQ represent the asymmetric forms (A12) in muscle, while complexes with PRiMA represent tetrameric globular forms (G4) mainly found in brain and muscle. Apart from these traditional molecular forms, a ColQ-linked asymmetric form and a PRiMA-linked globular form of hybrid cholinesterases (ChEs), having both AChE and BChE catalytic subunits, were revealed in chicken brain and muscle. The similarity of various molecular forms of AChE and BChE raises interesting question regarding to their possible relationship in enzyme assembly and localization. The focus of this review is to provide current findings about the biosynthesis of different forms of ChEs together with their anchoring proteins.